Fujita exponents for a space–time weighted parabolic problem in bounded domains. (December 2021) - Sun, Xizheng; Liu, Bingchen; Li, Fengjie
Abstract: This paper deals with a semilinear weighted parabolic problem in general bounded domains, subject to zero Dirichlet boundary conditions, where the weighted functions depend not only on space variable but also on time variable. Fujita exponents for blow-up and global existence of solutions are determined by using semigroup methods and the comparison principle, which are composed by the dimensions of the space domains and the eight exponents in nonlinear coupled sources and the space–time weighted functions.